2013
DOI: 10.1093/ejcts/ezs668
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted vs open mediastinal lymphadenectomy for Stage I non-small-cell lung cancer: results of a prospective randomized trial†

Abstract: Mediastinal lymph node dissection can be performed as effectively by the video-assisted approach as by the open thoracotomy approach. Furthermore, the video-assisted approach allows a better visualization of different lymph node zones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 13 publications
1
46
1
Order By: Relevance
“…3,4,6) In a multicenter study, D'Amico et al 5) compared 199 patients undergoing VATS with 189 patients undergoing T, and found similar results. Unlike the previous studies concerning of patients with N0 diseases, the latter one included also patients with N2 and N3 diseases.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…3,4,6) In a multicenter study, D'Amico et al 5) compared 199 patients undergoing VATS with 189 patients undergoing T, and found similar results. Unlike the previous studies concerning of patients with N0 diseases, the latter one included also patients with N2 and N3 diseases.…”
Section: Discussionmentioning
confidence: 90%
“…In 2013, Palade et al 6) published their study compairing VATS and open mediastinal lymphadenectomy. They classified N1 and N2-level lymph nodes into different zones, and made a detailed comparison between two approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palade et al had carried out a prospective randomized controlled study on the effectiveness of MLN dissection under VATS (17). The results indicated that operation time was distinctly shorter in VATS group, with the The results revealed that the average MLN numbers and group numbers were 22.5 and 5.0, respectively, and no one was converted into thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Some controversies still exist with regard to the quality of minimally invasive sLND. While the number of dissected lymph nodes (LN) in VATS procedures is equal to the open approach, the nodal upstaging rate from clinical to pathological N-factor has been reported to be lower after a VATS approach [7][8][9].…”
mentioning
confidence: 99%